Study of the influence of the vitamin-mineral complex "Silicon active" on the condition of the periodontal tissues of rats during the modeling of periodontitis - Schnaider, S. A.; Anisimov, M. V.; Maslov, A. V.; Tkachenko, E. K. (Journal of Education, Health and Sport, 2017)
The purpose of the research was to study the effects of the vitamin-mineral complex "Silicon Active" on the condition of periodontal tissues of rats under the conditions of modeling periodontitis with the help of exogenous hyaluronidase. The experiment was carried out on 21 female rats 1 month old. age line Wistar, divided into 3 groups. The first group is intact (5 individuals). Rats of the 2nd group (control, 8 individuals) and group 3 modeled the periodontal pathology by inserting a lidase solution under the gums of the rats. In the third group (8 individuals), against the backdrop of modeling periodontitis, rats were given per os vitamin-mineral complex "Silicon active". The duration of the experiment was 55 days. Vitamin-mineral complex "Silicon active", applied orally in rats under the conditions of parodontitis modeling, restored the structural and functional state of the connective tissue of periodontium of the rats disrupted during the modeling.